A missense mutation sheds light on a novel structure–function relationship of RANKL. Issue 4 (23rd September 2020) - Qiu, Heng; Qin, An; Cheng, Taksum; Chim, Shek M.; Smithers, Luke; Chen, Kai; Song, Dezhi; Liu, Qian; Zhao, Jinmin; Wang, Chao; Teguh, Dian; Zhang, Ge; et al.
Abstract: The tumor necrosis factor (TNF)‐like core domain of receptor activator of nuclear factor‐κB ligand (RANKL) is a functional domain critical for osteoclast differentiation. One of the missense mutations identified in patients with osteoclast‐poor autosomal recessive osteopetrosis (ARO) is located in residue methionine 199 that is replaced with lysine (M199K) amid the TNF‐like core domain. However, the structure–function relationship of this mutation is not clear. Sequence‐based alignment revealed that the fragment containing human M199 is highly conserved and equivalent to M200 in rat. Using site‐directed mutagenesis, we generated three recombinant RANKL mutants M200K/A/E (M200s) by replacing the methionine 200 with lysine (M200K), alanine (M200A), and glutamic acid (M200E), representative of distinct physical properties. TRAcP staining and bone pit assay showed that M200s failed to support osteoclast formation and bone resorption, accompanied by impaired osteoclast‐related signal transduction. However, no antagonistic effect was found in M200s against wild‐type rat RANKL. Analysis of the crystal structure of RANKL predicted that this methionine residue is located within the hydrophobic core of the protein, thus, likely to be crucial for protein folding and stability. Consistently, differential scanning fluorimetry analysis suggested that M200s were less stable. Western blot analysis analyses further revealed impaired RANKL trimerization by M200s. Furthermore, receptor–ligand binding assay displayed interrupted interaction of M200s to its intrinsic receptors. Collectively, our studies revealed the molecular basis of human M199‐induced ARO and elucidated the indispensable role of rodent residue M200 (equivalent to human M199) for the RANKL function. Abstract : A single nucleotide replacement (596T‐A) at TNFSF11 located in chromosome 13 exon 8 leads to a missense mutation (Met199Lys) in the human receptor activator of nuclear factor‐κB ligand (RANKL). This substitution introduced a longer side chain and a positive charge into RANKL hydrophobic pocket, compromising RANKL's structural integrity. Misfolded RANKL results in impotent osteoclasts, causing osteopetrosis required life‐long treatment to maintain patients' life.